Investigação do fenômeno de pré-ignição a baixas velocidades em motor de ignição por centelha - Vitor Alvarenga Torres (2018)
Low-speed-pre-ignition (LSPI) presents a great challenge for developing smaller, more efficient internal combustion engines. Its causes and related mechanisms are not yet fully understood and the literature review indicates varying results for each particular engine. With the objective of assessing the inuence of calibration and operation engine parameters on the occurrance of LSPI and searching for potential solutions, a methodology for investigating the phenomenon is developed, using indicated pressure data in order to evaluate LSPI occurrance and intensity paired with in-cylinder light intensity analysis during combustion in order to dene the regions of higher occurance of abnormal combustion phenomena. For the purposes of this work, a naturally aspirated, ex-fuel 1.0L SI PFI engine with a compression ratio of 13:1 was used. The given data yields good evidence of the main mechanism causing LSPI and the spatial analysis allows the evaluation of possiblemodications to the combustion chamber, intake manifolds, valve design and valve event maps. Guidelines for result interpretation are also presented. The ease of instrumentation and test-bed setup makes this methodology useful for pre-ignition diagnosis in a broad variety of engines, both commercial and experimental. The obtained results indicate that altering the cooling uid temperature has the largest inuence on LSPI occurrance and intensity. It is concluded that the presence of hotspots on the combustion chamber is the main mechanism causing LSPI in the test engine, and that the kinetic chemistry of the mixture also plays an important role in abnormal combustion occurance